1978
DOI: 10.1029/jc083ic07p03617
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies of wind‐driven Langmuir circulations

Abstract: Langmuir circulations in a wind wave tank have been observed and measured by a variety of methods including dye patterns and floating surface tracers. On the basis of measurements of cellular wavelength λc as a function of surface wavelength λw and depth H a tentative functional relation for the dependence of λc/H upon λw/H is proposed. The experiments clearly imply that the waves play an important role in the mechanism of formation of the Langmuir circulations but that the depth of the layer has a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(33 citation statements)
references
References 10 publications
(8 reference statements)
2
31
0
Order By: Relevance
“…At this point, Faller and Caponi (1978) undertook more laboratory studies and, in addition to introducing the terminology "CL-1" and "CL-2" for the first and second editions of the Craik-Leibovich analyses, showed that both mechanisms do, in fact, produce rolls in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…At this point, Faller and Caponi (1978) undertook more laboratory studies and, in addition to introducing the terminology "CL-1" and "CL-2" for the first and second editions of the Craik-Leibovich analyses, showed that both mechanisms do, in fact, produce rolls in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Their existence has been noted for some time (Langmuir 1938), and many explanations have been suggested (Scott et al 1969;Pollard 1977). The theory of gcnelmation by intersecting wave trains (Craik and Leibovich 1976) has received exp,?rimental support (Faller 1978;Faller and Caponi 1978). In this paper we sl-all ignore downwind transport and consider only movement in a vertical cro:;s-section perpendicular to the axis.…”
mentioning
confidence: 99%
“…Matsunaga and Uzaki [16] visualized the streaky structure in a laboratory flume, in the same manner as Faller and Caponi [8], and pointed out that not a water wave but the flow instability may induce large scale circulation. In their experiments, the secondary currents were induced only by wind shear (i.e., no wave condition), implying that the CL2 model should be sufficiently examined.…”
Section: Introductionmentioning
confidence: 93%
“…The theory proposed by Craik and Leibovich [7] is called CL2, and has been supported by many researchers. Faller and Caponi [8] conducted laboratory experiments to visualize the streaky structure within a horizontal plane; they postulated the presence of circulation, and pointed out the relationship between streak spacing and wind speed. In the natural ocean, such streaky structures are often observed (see Thorpe's [9] in depth review).…”
Section: Introductionmentioning
confidence: 99%